Mathematical modeling in scheduling cancer treatment with combination of VEGF inhibitor and chemotherapy drugs. (7th February 2019) - Lai, Xiulan; Friedman, Avner
Highlights: A mathematical model is developed to describe the interactions between two anticancer drugs in the treatment of metastatic breast cancer. Since one of the drugs (anti-VEGF) is antagonistic to the other (chemotherapy drug), we address the question how to schedule the treatment in order to reduce antagonism and increase treatment efficacy. In contrast with common approach to administer the two drugs at the same time, we show that administering the two drugs non-overlappingly yields significant better benefits. Abstract: The present paper considers a treatment of cancer with a combination of anti-VEGF (bevacizumab) and a chemotherapy drug (docetaxel). Since anti-VEGF reduces the perfusion of chemotherapy drugs, the question arises whether it is more effective to administer the two drugs at the same time, or non-overlapping, in order to reduce tumor volume more effectively. To address this question we develop a mathematical model and use it to simulate different schedules. We find that the treatment of cancer would be far more effective if the two drugs are given non-overlappingly, with the chemotherapy drug at day 0 and anti-VEGF at day 7 in cycles of 21 days.